Mental skills training: Psychological considerations of performance - Silby, C. (The science of figure skating, 2018)
Athletes know that to create skating outcomes that match their capabilities, mental training must be included regularly in their training and competition routines. Typically, athletes are seeking to feel more control of their performance levels, perform consistently to their abilities, and feel confident about their ability to deliver high-level performances in critical moments. Mental training provides athletes the coping skills of focusing on the controllable aspects of performance, finding perspective through factual appraisals, responding to appropriate cues, and increasing confidence using self-talk. Ultimately, the foundation for mental training can be laid in early childhood when we begin to teach emotional control. As children mature, more advanced coping strategies can be introduced and refined to meet the specific cognitive, emotional, and performance challenges presented by each stage in a young person's development. Developing mental fitness skills will not guarantee athletic success; instead, it is the foundation for an empowering sport experience that leads to the best chance of reaching their goals and enjoying the process.